A study on sales Force management system (Project Outreach) of Philip Morris Bangladesh Limited - Hasan, S M Mahmudul (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.